Minimization of Audit Report Lag through Corporate Governance and Audit Matters: Empirical Study on LQ 45 Companies Listed on the Indonesia Stock Exchange - Wahjono, Agus; Danardono, Indri Kartika (Journal of Advanced Multidisciplinary Research, 2024)
Timely publication of financial statements needs to be done by companies so that stakeholders can make decisions according to their needs. This study uses a quantitative approach to explore how corporate governance and audit matters affect the length of time for financial report publication. The research population came from LQ-45 index companies and listed on the Indonesia Stock Exchange (IDX) in 2020-2022 which were analyzed using Multiple Linear Regression Analysis. The purposive sampling technique was used to select 90 research samples. This study uses secondary data from the official website of the Indonesia Stock Exchange (IDX) and the company's official website. The findings of this study are that the audit committee and independent commissioners have a significant negative effect on audit report lag, but key audit matters show an insignificant negative effect. Future research is expected to expand the sample to other industries or examine factors such as business complexity, level of regulation, and economic conditions. This research has important implications for the government, OJK, companies, and KAP. The government and OJK can design policies to encourage effective corporate governance practices, while companies and KAP can use the results of this study as motivation to increase transparency and accountability in audit reports.